Developing a Systematic, Cross-Faculty Approach to Teaching and Assessing Reflection in Higher Education : Final Report. - Ryan, Mary; Ryan, Michael (Australian Learning and Teaching Council (ALTC), 2012)
Final report from a project that developed staff and student capacities for teaching and learning reflective writing in higher education. A model and accompanying resources were developed to support assistant deans (teaching and learning) and course coordinators to embed a systematic and developmental, evidenced-based, whole-course approach to the teaching and assessment of reflective writing for the purpose of transformative professional practice. The project embedded a model of good reflective practice across courses that support portfolio submissions, work integrated learning, transitions into university, and transition from higher education into the professions. It developed essential skills for academic staff and students, to support the widespread introduction of the e-portfolio as an assessment item within units, and as a capstone assessment of professional practice and standards within courses. This was achieved by working collaboratively across the disciplines of education, law, health, creative industries and business at Queensland University of Technology, with potential for widespread adoption across the sector.